Leptospirosis: a diagnostic conundrum. (October 2018) - Gurumurthy, Keerthivasan; Narasimha, Harish Belgode; Wyawahare, Mukta; Biswal, Niranjan
Leptospirosis is a serious public health concern worldwide. It is highly endemic in the Andaman Islands and its prevalence is increasing in other Indian states. Clinical features are non-specific and diagnosis relies on laboratory confirmation. The gold standard is microscopic agglutination testing, but this is not widely available. Real-time polymerase chain reaction testing of LipL32 antigen provides the earliest detection of pathogenic Leptospira in the body. We found it to be 100% specific, but it should be used in the first 10 days of illness for reliable results.